2021
DOI: 10.3393/ac.2020.08.03
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between High-Output Stomas, Postoperative Ileus, and Readmission After Rectal Cancer Surgery With Diverting Ileostomy

Abstract: This study aimed to evaluate the relationship between high-output stomas (HOSs), postoperative ileus (POI), and readmission after rectal cancer surgery with diverting ileostomy. Methods: We included 302 patients with rectal cancer who underwent restorative resection with diverting ileostomy between January 2011 and December 2015. HOSs were defined as stomas with ≥2000 mL/day output. We analyzed predictive factors for readmission of these patients. Results: Forty-eight (15.9%) patients had HOSs during the hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Diverting ileostomies may reduce the clinical severity of anastomotic leakage, but no reduction of leakages is seen in the case of rectal cancer, remaining a controversial topic ( 40 ). Especially high output diverting ileostomies are suspected to be at risk for POI, readmission, and subsequent ileus ( 40 ). In ovarian cancer, anastomoses are generally 3 cm–5 cm higher than in rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Diverting ileostomies may reduce the clinical severity of anastomotic leakage, but no reduction of leakages is seen in the case of rectal cancer, remaining a controversial topic ( 40 ). Especially high output diverting ileostomies are suspected to be at risk for POI, readmission, and subsequent ileus ( 40 ). In ovarian cancer, anastomoses are generally 3 cm–5 cm higher than in rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, older patients exhibited a high incidence of postoperative ileus and a relatively high rate of stoma formation. These conditions can be associated with high output and may increase the likelihood of low adherence to the ERAS protocol [39].…”
Section: Enhanced Recovery After Surgery In Specific Situationsmentioning
confidence: 99%
“…The incidence of HOS varies from 14% to 24%[ 29 , 41 - 43 ] with various definitions. The majority of previous reports have defined using specific values of output volume with a timeframe, such as 2000 mL per day[ 38 , 44 , 45 ], 1500 mL per day for two days[ 41 ], 1000 mL per day for three days[ 42 , 46 ], and 2000 mL per day for three days[ 29 , 43 ]. Some authors have used a combination of output volume with laboratory findings of renal impairment and/or physical signs of dehydration[ 36 , 47 ].…”
Section: Secretory Complication (High Output)mentioning
confidence: 99%
“…The causes of HOS are multifactorial, including factors associated with patients[ 42 , 48 ], disease[ 29 , 42 , 43 ], anatomy[ 29 ], surgical procedure[ 29 , 42 , 43 , 48 ], medication[ 29 , 33 ], nutrition[ 29 ], enteritis/metabolism[ 29 , 39 ] and those related to postoperative complications[ 29 , 44 , 49 ]. Older age was identified as an independent risk factor of HOS in two studies: however, the cut-off values were not shown because the comparisons were made without dichotomization in their studies[ 42 , 48 ].…”
Section: Secretory Complication (High Output)mentioning
confidence: 99%
See 1 more Smart Citation